Integrating Shape Cues of Adiposity and Color Information When Judging Facial Health and Attractiveness. (June 2014) - Fisher, Claire I; Hahn, Amanda C; DeBruine, Lisa M; Jones, Benedict C
Facial cues of adiposity play an important role in social perceptions, such as health and attractiveness judgments. Although relatively low levels of adiposity are generally associated with good health, low levels of adiposity are also a symptom of many communicable diseases. Consequently, it may be important to distinguish between individuals displaying low levels of facial adiposity because they are in good physical condition and those displaying low levels of facial adiposity because they are ill. Integrating information from facial cues of adiposity with information from other health cues, such as facial coloration, may facilitate such distinctions. Here, participants rated the health and attractiveness of face images experimentally manipulated to vary in shape cues of adiposity and color cues associated with perceived health. As we had predicted, the extent to which faces with low levels of adiposity were rated more positively than faces with relatively high levels of adiposity was greater for faces with healthy color cues than it was for faces with unhealthy color cues. Such interactions highlight the integrative processes that allow us to distinguish between healthy and unhealthy individuals during social interactions, potentially reducing the likelihood of contracting infectious diseases.